Species diversity and spatial differentiation of heritage trees in Chengdu, China - Yang, Yuanzhao; Sang, Shiye; Liu, Fangling; Xu, Yang; Jiang, Zhuying; Liu, Xiaoli (Frontiers in Ecology and Evolution, 2024)
IntroductionHeritage trees have special historical, cultural, and landscape value in cities and are keystone ecological structures for urban areas. However, these trees are threatened by rapid urbanization. To facilitate the conservation and management of such trees, our study investigated ancient trees in Chengdu, which is one of the hotspot of biodiversity and Historical and Cultural cities in Southwest of China.MethodsThe floristic diversity, Shannon-Wiener index (H), spatial pattern, characteristics, dimension, age, and health status of the trees were estimated by using ecological indexes and mathematical statistics.ResultsA total of 9383 heritage trees belonging to 119 species in 20 districts of Chengdu were surveyed. Dujiangyan (DJY) had the largest Shannon-Weiner index (H) (2.63), species count (76), and tree count (1842) and is therefore the most important district for preserving ancient trees. In contrast, Qingyang (QY) had the largest density of trees (120 trees/10 km2) among the 20 studied districts. In terms of important species, Phoebe zhennan (2351) was the dominant species, followed by Cupressus funebris, Ginkgo biloba, and Ficus virens. Akaike information criterion weights and standard deviation ellipse analysis showed that mean annual rainfall is a critical predictor for species distribution and age.DiscussionFindings from this study suggest that reducing water stress environments will improve the management and conservation of heritage trees in the future.